SELF-IMAGE AND SEXUAL ACTIVITY OF PATIENTS IN TREATMENT FOR BREAST CANCER: A SYSTEMATIC REVIEW - Abreu, Sam’la Helou Aly; Tanimitsu, Larissa Yurie Rezende; Issa, Guilherme Antonio Caixeta; Nobre, Ester Faustino Porfàrio; Nascimento, Danielle Brandão (CIPEEX, 2022)
BREAST ADENOCARCINOMA IS A TYPE OF CANCER WHICH SEVERELY IMPACTS A WOMAN€™S LIFE, BOTH PHYSICALLY AND PSYCHOSOCIALLY. THIS TYPE OF CANCER IS CAPABLE OF IMPACTING SELF-CONCEPT, FEMALE SEXUALITY AND EVEN FEMININITY. SEVERAL WOMEN DURING BREAST CANCER TREATMENT POSSESS A SELF-CONCEPT DISORDER DUE TO THE BREAST SOCIAL CONSTRUCT AS AN IMPORTANT AND SYMBOLIC ORGAN FOR FEMININITY, THUS IMPACTING SELF-ESTEEM OF PATIENTS WHO FEEL INSECURE IN THEIR SOCIAL AND MARITAL RELATIONSHIPS. THEREFORE, THE AIM OF THIS STUDY IS TO VERIFY THE INFLUENCES OF THERAPY AGAINST BREAST CANCER ON THE PSYCHOEMOTIONAL DIMENSION AND FEMALE SEXUALITY. A LITERATURE REVIEW WAS PERFORMED USING SCIENTIFIC PAPERS PUBLISHED BETWEEN 2011 AND 2021, AVAILABLE ON THE FOLLOWING DATA BASES SCIENTIFIC ELECTRONIC LIBRARY ONLINE, PUBLIC MEDLINE, BIBLIOTECA VIRTUAL EM SAÚDE AND PERIÓDICOS ELETRNICOS EM PSICOLOGIA. THE SEARCH SELECTED 81PAPERS IN TOTAL, WHICH WERE ASSESSED BY TWO REVIEWERS WITH RESPECT TO EXCLUSION AND INCLUSION CRITERIA, FINALLY 32 PAPERS WERE SELECTED, WHOSE CONTENTS WERE CATEGORIZED ACCORDINGLY TO THEMATIC CONTENT ANALYSIS. THE RESULTS OF THIS STUDY INDICATED THAT WOMEN SUBJECTED TO CANCER TREATMENT PRESENT THEMSELVES WITH PSYCHOSOCIAL DISORDERS DUE NOT ONLY TO THE BREAST NEOPLASM AND ITS AGGRESSIVE TREATMENT BUT ALSO TO BODY DISTORTION RESULTING FROM THE ENROLLMENT OF THE MAIN REPRESENTATIVE ORGAN OF FEMALE SEXUALITY. HENCE, THIS STUDY AIMS AT CONTRIBUTING TO THE SCIENTIFIC COMMUNITY, HELPING TO THE MAKING OF KNOWLEDGE REFERRING TO THE THEMATIC IN CONSIDERATION. KEYWORDS: SEXUALITY ;QUALITY OF LIFE; BREAST NEOPLASMS ; BODY IMAGE.